Village economic opportunity, forest dependence, and rural livelihoods in East Kalimantan, Indonesia - Dewi, S.; Belcher, B.; Puntodewo, A. (2005)
The changing role of forests in people’s livelihoods in frontier areas is important from the perspective of poverty alleviation and forest conservation. This study explores the link between expanding economic opportunities, forest dependence, and welfare in 73 villages. Village economic options, forest cover, and land suitability for agriculture and forestry are determining factors of people’s well-being. Increased accessibility to markets and deforestation are strongly associated with economic diversity at the village level. Increased economic diversity, larger areas of forests, more intensive land use, higher endowments of agricultural land and forest, and higher village population are related to increased well-being.